2017
DOI: 10.1089/thy.2017.0111
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of 3-Iodothyronamine and Derivatives in Biological Matrixes: Problems and Pitfalls

Abstract: These results suggest binding and sequestration of T1AM and/or its aldehyde derivative by blood and tissue proteins, with significant isotope effects. These issues might account for the technical problems complicating the analytical assays of endogenous T1AM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Previous studies have indicated that 3-T1AM is an effective metabolite product of the TH that can decrease the heart rate and lower the cardiac output [ 16 18 ]. We speculated that cardiomyocytes would be an essential target site for 3-T1AM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that 3-T1AM is an effective metabolite product of the TH that can decrease the heart rate and lower the cardiac output [ 16 18 ]. We speculated that cardiomyocytes would be an essential target site for 3-T1AM.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, analysis of 3-T1AM content of various tissues of rodents in several laboratories revealed remarkably high 3-T1AM concentrations in selected tissues, which might even approach those of tissue T4 and T3. The analytical issues related to this challenging task to determine circulating 3-T1AM concentrations have been addressed and discussed in several publications and recent reviews [6,7,18,79]. Apart from method-related issues (not yet solved) several hypotheses have been proposed to explain why 3-T1AM determination in blood of humans or animal experimental models has not revealed a uniform agreement.…”
Section: Biosynthesis Of 35-t2 and 3-t1am From Thm Precursors In Hummentioning
confidence: 99%
“…Previous studies have indicated that T1AM is an effective metabolite products of the TH that can decrease heart rate, lower cardiac output, and lower body temperature [19][20][21]. The effects of T1AM via TAAR1/TAAR2 at nanomolar concentrations were reported.…”
Section: Discussionmentioning
confidence: 99%